Dynamics of mental capacity of schoolchildren during study in secondary school under conditions of implementation of various educational programs - Sotnikova-Meleshkina, Zhanna; Havrylova, Tetiana; Zinchuk, Olha; Dudnyk, Iryna (ScienceRise: Medical Science, 2022)
The aim: to describe the dynamic changes in mental capacity during education in secondary school in the implementation of traditional and meritocratic educational program. Materials and methods. The study involved 56 secondary schoolchildren in the dynamics of learning, which were divided into 2 groups depending on the education system. The level of mental capacity was assessed using proofreading tests of V. Ya. Anfimov. Statistical data processing was performed using one-way analysis of variance and t-test in the software package IBM SPSS Statistics 20. Results. During the period of basic education, the level of influence of the type of educational program, type of subject and day of the week on the accuracy of the test performance increased, the amount of work increased by 16.2-16.7 % (p<0.01) and its accuracy decreased (p<0,05). Higher initial and post-load intensity of mental capacity was revealed in schoolchildren with meritocratic education (353.23±8.52 and 341.41±8.65 respectively), and with a traditional system - higher and stable accuracy (5.68-5.86 errors) and productivity of mental work (35.29-35.72 conventional units; p<0.01). The weekly efficiency curve was the opposite in terms of accuracy for 6th and 9th grade schoolchildren, and the identical in terms of volume. In meritocratic education, a higher level of intensity was registered in the mathematics lesson, and in the traditional educational program − accuracy against the background of negative dynamics of quantitative and complex indicators. Conclusions. Gender and age features of intensity, accuracy and productivity of mental work during basic education and the level of influence of factors of the educational process on them are established. The increase in the level of educational load was accompanied by an increase in the intensity and accuracy of mental work due to the adaptation of schoolchildren to the peculiarities of learning in secondary school and the stabilization of physiological processes. Comparison of weekly curves of mental capacity during training allowed to identify certain age trends in the formation of mental fatigue